TERAPI SENI UNTUK MENGATASI GANGGUAN KECEMASAN PADA LANSIA AKIBAT PANDEMI COVID-19 - Shokiyah, Nunuk Nur; Syamsiar, Syamsiar (Acintya, 2021)
The Covid-19 virus is still spreading throughout the world.  In fact, many are worried about being exposed to this virus, especially the elderly.  Anxious feelings due to excessive Covid-19 will lower his immunity.  Over time, this anxiety disorder can get worse and interfere with the sufferer's quality of life, therefore anxiety needs to be managed.  One way to deal with anxiety is through art therapy.Art therapy used in this study is through drawing and fruit creation, where the media used for art therapy is in accordance with the one chosen by the participants.  This study used a qualitative analysis based on: Self Report (Interview and Anxiety Scale using the measurement of anxiety levels using the TMAS (Taylor Manifest Anxiety Scale) instrument compiled and developed by Tylor, given three times, namely (pretest, posttest and follow up).  Ratiing By other, and Observation (Re-checting). The results of this study indicate a change in anxiety levels before and after the intervention.  Evidence obtained from the four participants shows a change in the total value of anxiety.  Thus, art therapy has been shown to reduce anxiety in the elderly due to the Covid-19 pandemicKeywords: Art therapy, Anxiety Disorders and Covid-19